Dynamics of Matrix Metalloproteinases in Local Cold Injury - M. I. Mikhailichenko (Scientific Сentre for Family Health and Human Reproduction Problems, 2019)
The relevance of cold injury is due to its high specific weight in the structure of injuries, complexities of complex therapy, and unsatisfactory results of treatment. It is known that in the pathogenesis of local cold injury, the leading role belongs to endothelial dysfunction, which secretes a huge amount of biologically active substances, including matrix metalloproteinases.Aim: to determine the dynamics of the content of matrix metalloproteinases of the second subfamily (MMP-2, MMP-9) in the serum of patients with local cold injury.Materials and methods. The study included 80 patients (60 men, 20 women) with frostbite of the III–IV degree of the foot to the level of the lower third of the leg in the late reactive period and the period of granulation and epithelization.Results. In the late reactive period in patients with cryopreservation, the level of MMP-2 was 3.4 times higher relative to the control (p = 0.011), on day 30 MMP-2 values did not differ from the control parameters (p = 0.103). The level of collagenase B (MMP-9) in patients with local cold injury on day 5 was 14.5 times higher than the control parameters (p = 0.002), on day 30 – 12.5 times higher compared to the control group (p = 0.000094).Conclusion. During the analysis of the data obtained, we can think about the dual nature of collagenases during the processes of inflammation. In a situation of distress, collagenases prevent endothelial dysfunction by eliminating the cellular structures of the endothelium to ensure adequate metabolism in tissues. Their importance as markers of failure of adequate flow of reparative processes is not excluded.